Pemanfaatan bahan bakar gas LPG pada motor tempel nelayan di Desa Bontokanang Kabupaten Takalar - Sunardi Sunardi; Ahsan S. Mandra (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The PKM program in Bontokanang Village, SouthGalesong District, Takalar Regency aims to: (1) increaseknowledge and skills in assembling a converter kit for GasFuel (BBG) kits, (2) increase knowledge and skills inrepairing and maintaining machinery (motorbike) fishingboats, and (3) increase income of fishing communities. Themethods used include: observation, counseling (theory),training (practice), discussion, and evaluation. Theparticipants' absorption of material mastery was good and thiswas evident at the time of the training. There were around90% participants who could assemble the converter kitproperly and it can function as a converter for BBM to BBG.This training was without significant constraints and could beimplemented according to the expected target. However, inthe engine repair training, only about 60% of participantsmanaged to diagnose correctly, so that most of the trainingparticipants still had difficulty finding problems or sources ofengine failure. This is reasonable, as in the repair of themachine it does require a lot of training and assistance.